Crystal structure of cis-copper(II) complex with N-(di-n-propylcarbamothioyl)cyclohexanecarboxamide ligand - Gumus, Ilkay; Ozer, Cemal Koray; Vanderveer, Don; Arslan, Hakan (European Journal of Chemistry, 2016)
Copper(II) complex, cis-[Cu(L-κ2S,O)2] of N-(di-n-propylcarbamothioyl)cyclohexane carboxamide ligands (HL) has been synthesized and structurally characterized by various spectroscopic techniques and single crystal X-ray diffraction crystallography. The cis-[Cu(L-κ2S,O)2], C28H50CuN4O2S2: Monoclinic, space group P21/n (no. 14), a = 10.025(2) Å, b = 21.724(4) Å, c = 14.848(3) Å, β = 100.60(3)°, Z = 4, Dcalc = 1.259 g/cm3, 22069 reflections measured (5.88° ≤ 2Θ ≤ 50.2°), 5639 unique (Rint = 0.0630, Rsigma = 0.0678) which were used in all calculations. The final R1 was 0.0488 (≥2σ(I)) and wR2 was 0.1277 (all data). Single crystal analysis revealed that a square-planar coordination geometry is formed around the copper atom by two sulphur and two oxygen atoms of the related ligand, which are in a cis configuration.